Application of the MENTOR model to advance One Health by promoting bat conservation and reducing zoonotic spillover risk - Smith, Lindsay J.; Gelman, Nancy; O’Mara, M. Teague; Frick, Winifred F.; Ronis, Emily M.; Cameron, Kenneth N.; Gonzales, Amanda; Coleman, Jeremy T. H.; Reichard, Jonathan D.; de Wit, Luz A. (Frontiers in Conservation Science, 2024)
For few taxonomic groups do conservation efforts have such a disproportionate impact on biodiversity and human well-being as they do with bats. Bats face significant conservation challenges that affect their long-term viability, inhibit their ecosystem functions and services, and increase zoonotic spillover risks. Protecting bat populations and their habitats ultimately reduces these conservation threats, helps prevent pandemics, and supports essential ecosystem services. MENTOR-Bat is a fellowship program focused on strengthening technical, and leadership capacity in the Global South to promote healthy environments where bats and humans can coexist with reduced risks of pathogen transmission. Co-designed by the United States Fish and Wildlife Service (USFWS) and Bat Conservation International (BCI), MENTOR-Bat mirrors the One Health framework by featuring a transdisciplinary team of three mentors and nine fellows from Cameroon, Colombia, and Indonesia. Fellows and mentors receive academic and field-based training on bat ecology and conservation, One Health, human dimensions of conservation, behavior change, strategic communications, international policy, adaptive management, project planning, conservation leadership, and public health. Fellows will then design and implement team pilot projects to advance One Health and bat conservation in their respective countries. Program evaluation of MENTOR-Bat is based on Kirkpatrick's Hierarchy and focuses on measuring the development of established One Health core competences. By incorporating One Health and conservation within its activities, MENTOR-Bat can become a valuable programmatic template for transdisciplinary programming advancing evidence-based strategies for improving the well-being of bats, humans, and the environment.